Association between maltreatment and polydrug use among adolescents. (January 2016) - Alvarez-Alonso, M.J.; Jurado-Barba, R.; Martinez-Martin, N.; Espin-Jaime, J.C.; Bolaños-Porrero, C.; Ordoñez-Franco, A.; Rodriguez-Lopez, J.A.; Lora-Pablos, D.; de la Cruz-Bértolo, J.; Jimenez-Arriero, M.A.; Manzanares, J.; Rubio, G.
Abstract: Different studies have related sexual and physical abuse during childhood and adolescence to the development of substance abuse disorders. Nevertheless, we are not aware of the role that other more common maltreatment types, such as neglect, will play among the most risky pattern of consumption: the polydrug use. A clinical sample of 655 adolescents, divided into two groups: polydrug users and non-polydrug users, were assessed on their pattern of drug consumption, history of childhood maltreatment, current psychopathology and their family history of alcoholism. Polydrug users had a greater prevalence of all types of maltreatment, although the most associated to this group were sexual abuse and emotional neglect. Other relevant variables to adolescent consumption were: the diagnosis of depressive disorder, the presence of anxiety traits and the family history of alcohol dependence. Polydrug users have higher risks of having had problems during infancy and adolescence, such as maltreatment and other psychopathological conditions, with the addition of family history of alcoholism. Accordingly, practitioners should take into account that those variables may influence polydrug abuse because it is the most risky pattern for subsequent dependence of substances, and they should always be considered during treatment.